2010
DOI: 10.1021/ef100398z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Temperature on the Release of Inorganic Species during High-Temperature Gasification of Hard Coal

Abstract: Several volatile inorganic species are of concern in future integrated gasification combined cycle (IGCC) power systems because of their relation to erosion, corrosion, fouling, and slagging. The aim of this work was to obtain more information on the influence of the temperature on the release of Na, K, Cl, and S species during gasification. Therefore, six hard coals were gasified in lab-scale experiments in a helium/oxygen atmosphere at 1100, 1400, and 1700 °C. The results represent conditions in an entrained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…Although many efforts have been made to investigate the behavior of alkali metals during biomass thermal conversation, which might be affected by various factors like fuel composition, operating conditions, and the combustion system chose for conversion (Nutalapati et al, 2005), coal and biomass have completely different fuel properties. For instance, coal has a variety of inorganic constituents in major (e.g., Si, Al, and S), minor (e.g., Na, K, Cl, and Ca), and trace (e.g., Hg) amounts in variable quantities, mostly depending upon the coal rank and origin (Bläsing et al, 2010), while most biomass contains high contents of potassium (0.2-1.9 wt% on dry base) and chlorine (0.1-1.1 wt% on dry base) (Zheng et al, 2007). Therefore, it has a great significance to investigate the behavior of alkali metals and other related elements during co-combustion biomass with coal, both for the optimization of existing power plants and the development of future biomass and coal co-firing technology.…”
Section: Introductionmentioning
confidence: 99%
“…Although many efforts have been made to investigate the behavior of alkali metals during biomass thermal conversation, which might be affected by various factors like fuel composition, operating conditions, and the combustion system chose for conversion (Nutalapati et al, 2005), coal and biomass have completely different fuel properties. For instance, coal has a variety of inorganic constituents in major (e.g., Si, Al, and S), minor (e.g., Na, K, Cl, and Ca), and trace (e.g., Hg) amounts in variable quantities, mostly depending upon the coal rank and origin (Bläsing et al, 2010), while most biomass contains high contents of potassium (0.2-1.9 wt% on dry base) and chlorine (0.1-1.1 wt% on dry base) (Zheng et al, 2007). Therefore, it has a great significance to investigate the behavior of alkali metals and other related elements during co-combustion biomass with coal, both for the optimization of existing power plants and the development of future biomass and coal co-firing technology.…”
Section: Introductionmentioning
confidence: 99%
“…The details of the setup have already been published elsewhere. Only some brief information is given here. The experimental setup consisted of an atmospheric flow tube furnace, which was directly coupled to MBMS for in situ hot gas analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The total gas flow was set to 3000 mL/min. The atmospheric conditions simulate a gasification environment. The end of the alumina reactor was coupled directly to the MBMS device to sample the high-temperature gasification products, e.g., alkali metal, chlorine, and sulfur species, without quenching. A total of 100 mg of fuel or fuel blend was gasified in a single-run batch procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, the estimated yields of HCl as functions of λ were essentially similar (Figure 7d). It is well known that chlorine tends to react with gaseous alkali species, which precipitate as alkali chlorides as the syngas is cooled downstream of the gasification reactor [34]. The total alkali content (K + Na) of the hardwood bark was approximately 1.6 times the corresponding content of the softwood bark.…”
Section: Minor Syngas Components and Particlesmentioning
confidence: 99%
“…Furthermore, the yields of these elements seemed to increase with λ, which seems natural since a higher gasification temperature (at higher λ) should result in higher volatility of these elements. Because of the higher volatility, there is also a higher probability for gaseous alkali species (e.g., K(g), Na(g), KOH(g), NaOH(g)) to react with HCl(g) forming alkali chlorides that subsequently precipitated in the syngas as fly ash particles [34]. The theory that a larger proportion of Cl is bound to alkali chlorides at higher λ also supports the results for HCl(g), seen in Figure 7d, which showed that the yield of HCl(g) decreased with increased λ.…”
Section: Syngas Particulate Mattermentioning
confidence: 99%